The Effect of Electronic Word of Mouth on Social Media and The Attraction of Bena Traditional Village Tourism on Tourist Visiting Decisions - Jamu, Maria Endang; Sari, Santy Permata (Universitas Muhammadiyah Sorong, 2022)
The purpose of this research is to examine the impact of electronic word of mouth on social media, as well as the impact of tourist attractions in the traditional hamlet of Bena on visitor decision-making. The descriptive and quantitative research methods were applied. The sampling method utilized is purposive sampling, with the informants being visitors who have visited Bena's traditional village. The findings revealed that social media and electronic word of mouth (E-WOM) in tourism destinations influenced tourists' decisions to visit Bena's traditional village. The findings of this study suggest that pleasant experiences of visiting the Bena Traditional Village, which are shared on social media platforms such as Facebook, Instagram, and WhatsApp, have a significant impact on the number of visitors to these attractions by social media users.